Linear accelerator-based stereotactic radiosurgery in recurrent glioblastoma: A single center experience - Sirin Sait; Oysul Kaan; Surenkok Serdar; Sager Omer; Dincoglan Ferrat; Dirican Bahar; Beyzadeoglu Murat (Vojnosanitetski Pregled)
Background/Aim. Management of patients with recurrent glioblastoma (GB) comprises a therapeutic challenge in neurooncology owing to the aggressive nature of the disease with poor local control despite a combined modality treatment. The majority of cases recur within the highdose radiotherapy field limiting the use of conventional techniques for re-irradiation due to potential toxicity. Stereotactic radiosurgery (SRS) offers a viable noninvasive therapeutic option in palliative treatment of recurrent GB as a sophisticated modality with improved setup accuracy allowing the administration of high-dose, precise radiotherapy. The aim of the study was to, we report our experience with single-dose linear accelerator (LINAC) based SRS in the management of patients with recurrent GB. Methods. Between 1998 and 2010 a total of 19 patients with recurrent GB were treated using single-dose LINAC-based SRS. The median age was 47 (23-65) years at primary diagnosis. Karnofsky Performance Score was ≥ 70 for all the patients. The median planning target volume (PTV) was 13 (7-19) cc. The median marginal dose was 16 (10-19) Gy prescribed to the 80%-95% isodose line encompassing the planning target volume. The median follow-up time was 13 (2-59) months. Results. The median survival was 21 months and 9.3 months from the initial GB diagnosis and from SRS, respectively. The median progression-free survival from SRS was 5.7 months. All the patients tolerated radiosurgical treatment well without any Common Toxicity Criteria (CTC) grade > 2 acute side effects. Conclusion. Single-dose LINAC-based SRS is a safe and well- tolerated palliative therapeutic option in the management of patients with recurrent GB.